2006
DOI: 10.1007/s11524-006-9120-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Knowledge of and Willingness to Prescribe Naloxone to Reverse Accidental Opiate Overdose: Challenges and Opportunities

Abstract: Naloxone, the standard treatment for heroin overdose, is a safe and effective prescription drug commonly administered by emergency room physicians or first responders acting under standing orders of physicians. High rates of overdose deaths and widely accepted evidence that witnesses of heroin overdose are often unwilling or unable to call 9-1-1 has led to interventions in several US cities and abroad in which drug users are instructed in overdose rescue techniques and provided a Btake-homed ose of naloxone. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 46 publications
3
90
1
Order By: Relevance
“…Surveys in 2002-2003 demonstrated that few medical providers were knowledgeable about prescribing naloxone to prevent overdose, were willing to prescribe naloxone, or supported naloxone distribution. [20][21][22] While these surveys were conducted early in the overdose epidemic and did not focus on patients prescribed opioids, their findings suggest that there may be considerable barriers to naloxone prescribing in primary care. To better understand these barriers, we conducted a qualitative study to assess clinical staff's knowledge, attitudes and beliefs about overdose education and naloxone prescribing.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys in 2002-2003 demonstrated that few medical providers were knowledgeable about prescribing naloxone to prevent overdose, were willing to prescribe naloxone, or supported naloxone distribution. [20][21][22] While these surveys were conducted early in the overdose epidemic and did not focus on patients prescribed opioids, their findings suggest that there may be considerable barriers to naloxone prescribing in primary care. To better understand these barriers, we conducted a qualitative study to assess clinical staff's knowledge, attitudes and beliefs about overdose education and naloxone prescribing.…”
Section: Introductionmentioning
confidence: 99%
“…Even though an early survey of drug users had found that THN was unlikely to lead to increased heroin consumption , a common concern among providers was potential promotion of drug use (Ashworth, 2006;Tobin et al, 2005). Negative attitudes were revealed in surveys of Baltimore-based emergency service providers (Tobin et al, 2005) and physicians throughout the US who were likely involved in treatment of opioid users (Beletsky et al, 2007): most believed THN would not reduce drug-related deaths and reported they would never consider prescribing naloxone. A notable exception was a postal survey of New York-based clinicians of whom over a third were willing to prescribe naloxone (Coffin et al, 2003).…”
Section: Providers' Concernsmentioning
confidence: 99%
“…By contrast, another study found mixed results when comparing medical students with their age mates in the general population (Flaherty & Richman, 1993). The prevalence of SUDs among doctors and medical students is near to 14%, being specialities such as anaesthesiology, psychiatry and emergency medicine the most related with substance use problems (Beletsky et al, 2007;Choi, Tolova, Socha, & Samenow, 2013;Cottler et al, 2013;Rose, Campbell, & Skipper, 2014). As denial is a common feature among people with substance use problems, it might be expected that the exposure of medical residents to substance use (both regarding themselves and their circle of friends or family), would minimize their ability to self-detect them and seek help (Miller, Sheppard, Colenda, & Magen, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Research has linked attitudes and level of addiction treatment training (specifically harm-reduction approaches), to therapeutic outcomes (Beletsky et al, 2007;Deren, Kang, Mino, & Seewald, 2011;Gerlach & Caplehorn, 1999;Goddard, 2003). This points to the need of making an integrated change in medical internship programmes (Ding et al, 2005).…”
Section: Introductionmentioning
confidence: 99%